The role and types of modern linguistics in the xxi century - Krasnikov, D. S. (ТДАТУ, 2020)
Sociolinguistics studies the relationships between language and society. Scientists who conduct research in this area are engaged not only in the phonetic features of dialects, but also in national languages, the social characteristics of multilingualism, the relationship between language and social roles.
Keywords: sociolinguistics; phonetic features of dialects; discourse analysis